Engineering alternative isobutanol production platforms - Felpeto-Santero, Carmen (AMB Express, 2015)
A synthetic inducible operon (IbPSO) expressing alsS, ilvC, ilvD and kivD genes encoding a pathway capable to transform pyruvate into 2-isobutyraldehyde has been designed and two recombinant plasmids named pIZIbPSO and p424IbPSO were constructed. The IbPSO containing plasmids can generate in a single transformation event new recombinant isobutanol producer strains and are useful for testing as suitable hosts wild type bacteria in different culture media. In this way we found that Shimwellia blattae (p424IbPSO) was able to produce in flasks up to 6 g l(−1) of isobutanol using glucose as carbon source. Moreover, for the first time, we have demonstrated that isobutanol can be produced from sucrose using Escherichia coli W (ATCC9367) transformed with pIZIbPSO. These robust recombinant strains were also able to produce isobutanol from a raw carbon source like hydrolysed lignocellulosic biomass.